Cyclosporine Therapy as a Rescue Treatment in Steroid Refractory Acute Severe Ulcerative Colitis: A Real Life Data From a Tertiary Center - Evirgen, Sami; İliaz, Raim; Akyüz, Filiz; Çavuş, Bilger; Göktürk, Suut; Örmeci, Aslı; Mutluay Soyer, Özlem; Baran, Bülent; Pınarbaşı, Binnur; Karaca, Çetin; Demir, Kadir; Beşışık, Fatih; et al. (Turkish Journal of Gastroenterology, 2022)
Background: Cyclosporine is a rescue treatment alternative to avoid colectomy in corticosteroid refractory acute severe ulcerative colitis. In this study, we aimed to evaluate the long-term efficacy and safety of cyclosporine therapy in acute severe ulcerative colitis patients. Methods: Acute severe ulcerative colitis (basal Lichtiger score > 10) patients who did not respond to 40 mg intravenous methylpredniso- lone therapy after 3-5 days were included in the study. The presence of clinical response and remission was assessed at 1st week, 1st, 6th, and 12th month according to the Lichtiger index. Results: In this study, 40 patients, whose steroid refractory acute severe ulcerative colitis and basal Lichtiger score > 10 points were enrolled. The median disease duration was 49.3 months (2-204). All patients received cyclosporine for 132 ± 78 days (7-270). Clinical response was obtained on seventh day in 82.5%. The clinical response rates of the first and sixth months were 72.5% and 62.5%, respectively. A total of 17/40 (42.5%) patients underwent colectomy within 1 year. In the patients who underwent colectomy, the basal LS (14.2 ± 1.9 vs 12.3 ± 1.7) (P = .002) was higher and the basal hemoglobin value (11.8 ± 2.3 vs 10.1 ± 1.5) (P = .037) was lower than those who did not undergo colectomy. Conclusion: Our findings suggest that cyclosporine treatment may be successfully and safely used in steroid refractory acute severe ulcerative colitis patients. Cyclosporine is a drug that has recently started to come up again with the introduction of new maintenance treatments. Especially in patients who develop a loss of response to infliximab therapy, or where infliximab therapy is contraindicated, or who have azathioprine intolerance, or are unresponsive. Cite this article as: Evirgen S, İliaz R, Akyüz F, et al. Cyclosporine therapy as a rescue treatment in steroid refractory acute severe ulcerative colitis: A real life data from a tertiary center. Turk J Gastroenterol. 2022;33(6):463-469.